Amenaza de aborto como factor de riesgo para resultados obstétricos desfavorables en el Hospital Belén de Trujillo - Rodríguez Ascón, Larry José Luis (2014)
To demostrate that Threatened abortion is a risk factor for adverse pregnancy outcomes in “Hospital Belén de Trujillo”. Material and method: An analytical cohort study evaluated 152 pregnant women, between 20 and 35 years old and less than 4 parity; divided into two groups according to the presentation or not of threatened abortion was performed: exposed group (38 pregnant women) and no group exposed (114 pregnant women) in both group the presentation of adverse obstetric outcomes in the same gestation were evaluated, the statistical tests of association were performed using the Chi - square test of Pearson , and the relative risk with a confidence interval of 95 was calculated %. Results: The mean age in the exposed group was 27.64 ± 5.66 SD years old, and the mean age for the unexposed group was 24.5 ± 4.76 SD years old. 6% of the exposed and 29% of the unexposed had preterm delivery, 34% of the exposed and 11% of the unexposed had premature rupture of membranes, 16% of the exposed and 2% of non-hemorrhage was exposed in the third quarter, 5% of those exposed to 1% of the unexposed had preeclampsia; showing statistical significance as an important risk factor for preterm delivery (RR = 6.23, p < 0.05), premature rupture of membranes (RR = 4.04 p = 0.001) and antepartum hemorrhage (RR = 10.5 p = 0.001 ). Conclusions: Threatened abortion is a risk factor for the development of preterm labor, premature rupture of membranes and antepartum hemorrhage